EPID-21. EPIDEMIOLOGY AND RISK FACTORS OF PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS IN CHILDREN AND ADULTS IN THE MIAMI CANCER INSTITUTE (MCI) COHORT. (12th November 2021) - Ramirez-Menendez, Miguel; Israel, Shirlinka; Rubens, Muni; Fernandez, Alejandra; Diaz, Zuanel; Hall, Matthew; Mohler, Alexander; Kotecha, Rupesh; Odia, Yazmin
Abstract: BACKGROUND: Many epidemiological studies assess risk factors and incidence of primary CNS tumors in the United States; few describe the incidence in specific geographic locations. Environmental or ethnic/racial factors may affect the incidence of primary CNS tumors. Miami-Dade County (MDC) is an ethnically-diverse US county, with 69.4% Hispanic, 12.9% White Non-Hispanic, 15.5% Black Non-Hispanic, Asian 1.6%, 0.3% Native, and 0.3% other. We characterized primary CNS tumors at Miami Cancer Institute (MCI) relative to national reports. METHODS: We reviewed electronic medical records for all patients (n=1221) diagnosed with CNS tumors at MCI from 2017 to 2021. Descriptive and statistical analyses assessed environmental and clinical variables. RESULTS: Malignant CNS tumors account for 74% of MCI primary CNS tumors. Diffuse gliomas (41%), meningiomas (26%), and embryonal tumors (5%) were the most common histologies; embryonal tumors most common at younger ages (median: 18 years). The most abundant histological subtypes were glioblastoma (54%), benign meningioma (92%), and medulloblastoma (73%), respectively. Ethnic/racial composition of glioma patients at MCI was 55.9% Hispanic, 24.6% White Non-Hispanic, 6.4% Black Non-Hispanic, 1.8% Other Non-Hispanic, 1.3% Asian, 10% unreported, comparable to MDC. Compared to national averages, the age distribution at MCI was higher among lower grade gliomas (range: 15-96, Median: 61 years), yet lower for malignant gliomas (range: 1-93, median: 47 years). The incidence of malignant CNS tumors did not differ by gender; benign primary CNS tumors were significantly more frequent in females (245/324, 76%; p < 0.001). Smoking history did not associate with incidence of primary CNS tumors; 793/1221 (65%) self-reported as non-smoker. CONCLUSION: The ethnic/racial composition and incidence of primary CNS tumors by histology at MCI significantly differs from national CBTRUS database (Ostrom et al ). This cohort will be further characterized by genetic profiles, race, diet, allergies, family history, substance use, clinical trial enrollment, therapeutic modalities, and overall survival rate.